2020
DOI: 10.3847/2041-8213/aba6eb
|View full text |Cite
|
Sign up to set email alerts
|

Limits on the Spin–Orbit Angle and Atmospheric Escape for the 22 Myr Old Planet AU Mic b*

Abstract: We obtained spectra of the pre-main-sequence star AU Microscopii during a transit of its Neptune-sized planet to investigate its orbit and atmosphere. We used the high-dispersion near-infrared spectrograph InfraRed Doppler (IRD) on the Subaru telescope to detect the Doppler “shadow” from the planet and constrain the projected stellar obliquity. Modeling of the observed planetary Doppler shadow suggests a spin–orbit alignment of the system ( deg),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 58 publications
5
47
0
Order By: Relevance
“…TOI837 joins a number of other young planetary systems reported from TESS, including DSTucAb, HIP67522b, TOI1726, and AUMicb (Newton et al 2019;Addison et al 2020;Hirano et al 2020;Mann et al 2020;Martioli et al 2020;Montet et al 2020;Palle et al 2020;Plavchan et al 2020;Rizzuto et al 2020;Zhou et al 2020). In the space of planet sizes and ages, the top panel of Figure 11 shows that TOI837 is among the youngest transiting planets known.…”
Section: Discussionsupporting
confidence: 54%
“…TOI837 joins a number of other young planetary systems reported from TESS, including DSTucAb, HIP67522b, TOI1726, and AUMicb (Newton et al 2019;Addison et al 2020;Hirano et al 2020;Mann et al 2020;Martioli et al 2020;Montet et al 2020;Palle et al 2020;Plavchan et al 2020;Rizzuto et al 2020;Zhou et al 2020). In the space of planet sizes and ages, the top panel of Figure 11 shows that TOI837 is among the youngest transiting planets known.…”
Section: Discussionsupporting
confidence: 54%
“…The AU Mic host is an M1 star with a spatially resolved edge-on debris disk (Kalas et al 2004) and at least one transiting planet, AU Mic b (Plavchan et al 2020). This Neptune-size planet is in a 8.5-d prograde orbit aligned with the stellar rotation axis (Martioli et al 2020;Hirano et al 2020;Palle et al 2020). While Plavchan et al (2020) only reported an upper limit on the mass of AU Mic b, Klein et al (2021) measured 17.1 +4.7 −4.5 M ⊕ thanks to infrared observations secured with the SPIRou spectropolarimeter (Donati et al 2020).…”
Section: Introductionmentioning
confidence: 98%
“…Although hundreds of obliquities have been measured with the RM effect, the current list includes only three M dwarfs: GJ 436 (Bourrier et al 2018a), TRAPPIST-1 (Hirano et al 2020a), and AU Mic (Addison et al 2020;Hirano et al 2020b;Palle et al 2020). The obliquity of GJ 436b was found to be l =  -+ 72 24 33 , suggesting a strong misalignment, and AU Mic was found to be well aligned with the equator of its host star.…”
Section: Introductionmentioning
confidence: 99%